Eco-virological survey of aedes mosquito larvae in selected dengue outbreak areas in Malaysia - Rohani, A.; Azahary, A.R.A.; Malinda, M.; Zurainee, M.N.; Rozilawati, H.; Najdah, W.M.A.W.; Lee, H.L. (The Indian Council of Medical Research (ICMR), 2014)
Background & objectivesi: Transovarial transmission of dengue virus in the Aedes vectors is now a well-documented phenomenon reported from many parts of the endemic areas in the world, which played an important role in initiating and maintaining the outbreak in human populations. This study investigated the factors affecting breeding habitats and the relationship with transovarial dengue virus in larvae of Aedes aegypti and Ae. albopictus. Methods: Larval surveillance was conducted in dengue outbreak areas in Malaysia from 2008 until 2009. Sampling was carried out based on habitat type, water condition (substrate type), canopy coverage, temperature and pH at breeding habitats. RT-PCR was performed to detect presence of transovarial dengue virus in larvae collected in the study areas. Results: A total of 789 breeding habitats were identified during this study and the majority of these breeding sites were plastic containers (57.46%). Aedes albopictus dominated most of the water condition surveyed, while Ac. aegypti indicated preference toward habitats with clear water. Aedes aegypti was selective in selecting ovipositional sites compared to Ac. albopictus where shaded areas were shown to be the most preferred. From a total of 363 mosquito larvae pools, 23 (6.3%) pools were positive for dengue virus where 18 of them were from Ae. albopictus and five were from Ac. aegypti mosquito larvae pools. nterpretation & conclusion: This study indicated the presence of transovarial transmission of dengue virus in immature Ac. aegypti and Ac. albopictus in the field. This study also showed that combination of water conditions, canopy coverage, temperature and pH of breeding habitats were the factors affecting the larval population. The study suggested that larval survey programme could serve as a tool not only to monitor the local dengue vector distribution but also to provide objective information for taking appropriate action by the community against dengue vectors.